GAMBARAN KADAR HEMOGLOBIN DAN HEMATOKRIT PADA PASIEN IDIOPATHIC SCOLIOSIS DI POLIKLINIK ORTHOPEDI RSUP DR. M. DJAMIL PADANG - Taufik, Muhammad Muhtadi; Sahputra, Roni Eka; Nurhajjah, Siti; Noverial, Noverial; Rusdji, Dina Arfiani (SINERGI : Jurnal Riset Ilmiah, 2025)
Background: Idiopathic scoliosis can cause pulmonary dysfunction due to thoracic pressure that triggers hypoxia, theoretically increasing hemoglobin and hematocrit levels as a compensatory mechanism.  Objective: This study aims to describe the levels of hemoglobin and hematocrit in patients with idiopathic scoliosis at the Orthopedic Clinic of RSUP Dr. M. Djamil Padang. Methods: This research employed a descriptive retrospective method, collecting medical record data of idiopathic scoliosis patients from 2018 to 2022. The data analyzed included age, gender, hemoglobin levels, and hematocrit levels prior to surgery. Out of 17 patients recorded, nine met the inclusion criteria. Results: The results showed that all patients were in the adolescent age category (10–18 years), with the highest age range being 14–16 years. All patients were female. A total of 44% of patients had hemoglobin levels of 13–14 g/dl, while 55% had hematocrit levels of 40–42%. Conclusion: The conclusion of this study is that there was no significant increase in hemoglobin and hematocrit levels before surgery, indicating no clear evidence of hypoxia compensation through elevated hemoglobin and hematocrit levels in patients with idiopathic scoliosis at RSUP Dr. M. Djamil Padang.